La música rap y su incidencia como manifestación cultural urbana en la ciudad de Riobamba periodo julio - diciembre 2020 - José Eduardo, Tenelema Daquilema (2021)
ABSTRACT The present research called "Rap Music and its Incidence as an Urban Cultural Manifestation in the city of Riobamba from July to December 2020" was carried out to identify the influence of rap music as an urban cultural manifestation in the city of Riobamba period July - December 2020. Through qualitative research, social coexistence, and gathering of information that helps to deepen the history of rap music in the city; Interviews were conducted with representatives of the hip hop movement of the country and the city, groups and mc's directly linked to rap music allowing us to know the reality of the genre in the city of Riobamba. From the analysis of the interviews carried out, it was found that this genre has come to influence the behavior of the interviewees in one way or another and changed the way they see the world. This includes their way of being and treating people. Rap music has a significant influence on people since they can express feelings, emotions, and thoughts. In addition, it also has an impact on ideology, identity, behavior, and clothing. Based on the opinion of the interviewees, it was the aspects that motivated them to follow this musical genre. Rap was a genre that helped raise the protest of African Americans and Latinos who lived in slums of New York and the Bronx in the '70s; it was the target of criticism and scandals for the interpreters' message in their songs. Keywords: rap, influence, culture, communication. Reviewed by: Mgs. Sonia Granizo Lara. English professor. c.c. 0602088890